Exenatide exerts a PKA-dependent positive inotropic effect in human atrial myocardium: GLP-1R mediated effects in human myocardium. (December 2015) - Wallner, Markus; Kolesnik, Ewald; Ablasser, Klemens; Khafaga, Mounir; Wakula, Paulina; Ljubojevic, Senka; Thon-Gutschi, Eva Maria; Sourij, Harald; Kapl, Martin; Edmunds, Nicholas J.; Kuzmiski, J. Brent; Griffith, David A.; et al.
Abstract: Glucagon-like peptide-1 receptor (GLP-1R) agonists are a rapidly growing class of drugs developed for treating type-2 diabetes mellitus. Patients with diabetes carry an up to 5-fold greater mortality risk compared to non-diabetic patients, mainly as a result of cardiovascular diseases. Although beneficial cardiovascular effects have been reported, exact mechanisms of GLP-1R-agonist action in the heart, especially in human myocardium, are poorly understood. The effects of GLP-1R-agonists (exenatide, GLP-1(7–36)NH2, PF-06446009, PF-06446667) on cardiac contractility were tested in non-failing atrial and ventricular trabeculae from 72 patients. The GLP-1(7–36)NH2 metabolite, GLP-1(9–36)NH2, was also examined. In electrically stimulated trabeculae, the effects of compounds on isometric force were measured in the absence and presence of pharmacological inhibitors of signal transduction pathways. The role of β-arrestin signaling was examined using a β-arrestin partial agonist, PF-06446667. Expression levels were tested by immunoblots. Translocation of GLP-1R downstream molecular targets, Epac2, GLUT-1 and GLUT-4, were assessed by fluorescence microscopy. All tested GLP-1R-agonists significantly increased developed force in human atrial trabeculae, whereas GLP-1(9–36)NH2 had no effect. Exendin(9–39)NH2, a GLP-1R-antagonist, and H-89 blunted the inotropic effect of exenatide. In addition, exenatide increased PKA-dependent phosphorylation of phospholamban (PLB), GLUT-1 and Epac2 translocation, but not GLUT-4 translocation. Exenatide failed to enhance contractility in ventricular myocardium. Quantitative real-time PCR (qRT-PCR) revealed a significant higher GLP-1R expression in the atrium compared to ventricle. Exenatide increased contractility in a dose-dependent manner via GLP-1R/cAMP/PKA pathway and induced GLUT-1 and Epac2 translocation in human atrial myocardium, but had no effect in ventricular myocardium. Therapeutic use of GLP-1R-agonists may therefore impart beneficial effects on myocardial function and remodelling. Highlights: Exenatide and GLP-1(7–36)NH2 increased contractility in human atrial myocardium. Inotropy is mediated through the GLP-1R/cAMP/PKA signaling pathway. Exenatide induced Epac2 and GLUT-1 translocation in atrial human myocardium. Exenatide failed to enhance contractility in human non-failing ventricular myocardium. GLP-1R is expressed in humans in atrial and ventricular myocardium